Cellulosimicrobium cellulans aortic prosthetic valve endocarditis. Issue 10 (21st December 2019) - Monticelli, Jacopo; Gerloni, Riccardo; Farina, Claudio; Knezevich, Anna; Dore, Franca; Luzzati, Roberto
Abstract : Introduction. Invasive infections due to Cellulosimicrobium spp. (a Gram-positive coryneform) are extremely rare. Only a few cases of bloodstream infections and endocarditis have been described, as bacteraemia due to coryneforms is usually discarded as blood culture contamination. Case presentation. A 66-year-old female, with a history of aortic valve replacement, presented with fever, left leg purpura and acute kidney injury. Multiple repeated blood cultures were positive for Cellulosimicrobium cellulans, and targeted therapy was started. At first, endocarditis was excluded by echocardiograms, and the acute nephritis was interpreted as an atypical presentation of Henoch–Shönlein purpura. High-dose prednisone was started, and after 10 weeks the patient presented again with fever, mental confusion and acute left arm ischaemia. A subsequent echocardiogram and radiolabelled leukocyte scintigraphic evaluation revealed aortic prosthetic valve endocarditis with periprosthetic abscess and arterial brachial thrombosis. The patient deceased, and the autoptic examination confirmed an aortic valve periprosthetic abscess and revealed multiple arterial thromboses and septic embolisms in the kidneys, brain, spleen and myocardium. Conclusion. Isolation of coryneform bacteria on blood culture should not always be discarded as blood culture contamination. In the case of endocarditis due to Cellulosimicrobium spp., the removal of any prosthetic material, along with prolonged in vitro active antimicrobial therapy, should be pursued in order to reduce persistence or relapses of infection.